Academic aspirations amongst sessional tutors in a New Zealand University - Sutherland, Kathryn; Gilbert, Amanda (Journal of University Teaching and Learning Practice, 2013)
In New Zealand, as in many other western societies, the higher education system has become an increasingly less secure place in which to work, and over 40 per cent of those teaching in New Zealand higher education are sessional staff of some kind. Our university in New Zealand has long relied on part-time paid tutors, many of whom are students themselves, to deliver part of the teaching in large courses. These tutors work with groups of students facilitating their learning in workshops, seminars, laboratories and a variety of other teaching environments. We have tracked the experiences of tutors over a significant period of time, and surveys of tutors’ experiences since 2007 reveal that the majority of respondents hold tight to the hope of a future academic career. They regard tutoring as good preparation for an academic career, and many report being even more committed to pursuing an academic career since beginning tutoring.How can we best support tutors to navigate their way into an academic career that might look somewhat different from the one they set out to pursue? This paper shares data and insights from our longitudinal research with tutors, and encourages those supporting sessional staff to think about how to enable tutors to take a scholarly approach to their teaching, regardless of the career path they eventually take.